Evaluation of In Vitro Antimalarial Activity of Different Extracts of Artemisia aucheri Boiss. and A. armeniaca Lam. and Fractions of the Most Potent Extracts - Mahdi Mojarrab; Ali Shiravand; Abbas Delazar; Fariba Heshmati Afshar (The Scientific World Journal)
Ten extracts with different polarity from two Iranian Artemisia species, A. armeniaca Lam. and A. aucheri Boiss, were screened for their antimalarial properties by in vitro  β-hematin formation assay. Dichloromethane (DCM) extracts of both plants showed significant antimalarial activities with IC50 values of 1.36 ± 0.01 and 1.83 ± 0.03 mg/mL and IC90 values of 2.12 ± 0.04 and 2.62 ± 0.09 mg/mL for A. armeniaca and A. aucheri, respectively. Bioactivity-guided fractionation of DCM extracts of both plants by vacuum liquid chromatography (VLC) over silica gel with solvent mixtures of increasing polarities afforded seven fractions. Two fractions from DCM extract of A. armeniaca and four fractions from DCM extract of A. aucheri showed potent antimalarial activity with reducing IC50 and IC90 values compared to extracts. The most potent fraction belonged to DCM extract of A. armeniaca with IC50 and IC90 values of 0.47 ± 0.006 and 0.71 ± 0.006 mg/mL, respectively.